2018
DOI: 10.20473/jbe.v6i12018.60-68
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Factor of Diabetic Neuropathy on Diabetes Mellitus Type 2 Patients

Abstract: Background: The prevalence of diabetes mellitus (DM) type 2 increased in 2013 by 2.10% from the previous years. It has been reported that the patients of diabetes type 2 patients in RSUD Dr. M. Soewandhi as a public hospital in Surabaya increased in 2014-2016.  Purpose: This study aimed to analyze the dominant factor of diabetic neuropathy in patients with DM type 2. Methods: The study design was case control by taking sample through systematic random sampling. There were 36 respondents contributed in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
2
5
0
11
Order By: Relevance
“…This study is the same with another study where the higher prevalence of diabetic neuropathy was found in groups without a family history [12]. In theory, stated that family history relates to diabetes mellitus where if one parent suffers from DM, a person's risk of developing DM is 15% if both parents have diabetes, the risk of developing DM increases to 75% [17].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study is the same with another study where the higher prevalence of diabetic neuropathy was found in groups without a family history [12]. In theory, stated that family history relates to diabetes mellitus where if one parent suffers from DM, a person's risk of developing DM is 15% if both parents have diabetes, the risk of developing DM increases to 75% [17].…”
Section: Discussionsupporting
confidence: 83%
“…The results of the study found that the prevalence of diabetic neuropathy was more prevalent in women ranging from 50.8% [4], [12]. Hormone differences in men and women affect the onset of neuropathy.…”
Section: Discussionmentioning
confidence: 86%
“…At the age of 45 years, body functions physiologically decline, this is due to a decrease in insulin secretion or resistance so that the ability of the body's to control high blood glucose is less than optimal 10 . Research by Hutapea 11 states that almost all ages who experience neuropathy the most are 45-65 years 12 . Other researchers also stated that the age range that experienced diabetic neuropathy was the most in the age range of 51 -59 years by 52,7% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Research by Hutapea 11 states that almost all ages who experience neuropathy the most are 45-65 years 12 . Other researchers also stated that the age range that experienced diabetic neuropathy was the most in the age range of 51 -59 years by 52,7% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Kadar gula yang tinggi menjadi penyebab 43 % kematian pada penderita DM usia di bawah 70 tahun. Tahun 1980 sampai dengan tahun 2014, trend peningkatan kejadian angka diabetes melitus meningkat secara signifikan [2]. WHO melaporkan bahwa setiap tahunya 1,6 juta kematian secara langsung dihubungkan dengan penyakit diabetes melitus dan kurang lebih 422 juta penduduk di diseluruh dunia menderita diabetes melitus.…”
Section: Pendahuluanunclassified